REP2: A Web Server to Detect Common Tandem Repeats in Protein Sequences. Issue 11 (28th May 2021) - Kamel, Mohamed; Kastano, Kristina; Mier, Pablo; Andrade-Navarro, Miguel A.
Highlights: Tandem repeats (TRs) in protein sequences are frequent but difficult to detect. We implemented a web server that uses a profile-based method to detect TRs. Protein sequences can be analysed for 11 types of common TRs. Proteins can be analysed separately or in multiple sequence alignments. We provide precomputed results for 78 UniProt reference proteomes. Abstract: Ensembles of tandem repeats (TRs) in protein sequences expand rapidly to form domains well suited for interactions with proteins. For this reason, they are relatively frequent. Some TRs have known structures and therefore it is advantageous to predict their presence in a protein sequence. However, since most TRs diverge quickly, their detection by classical sequence comparison algorithms is not very accurate. Previously, we developed a method and a web server that used curated profiles and thresholds for the detection of 11 common TRs. Here we present a new web server (REP2) that allows the analysis of TRs in both individual and aligned sequences. We provide currently precomputed analyses for a selection of 78 UniProt reference proteomes. We illustrate how these data can be used to study the evolution of TRs using comparative genomics. REP2 can be accessed at http://cbdm-01.zdv.uni-mainz.de/ munoz/rep/ .